Amygdala and regional volumes in treatment‐resistant versus nontreatment‐resistant depression patients. Issue 11 (9th August 2017) - Sandu, Anca‐Larisa; Artiges, Eric; Galinowski, André; Gallarda, Thierry; Bellivier, Frank; Lemaitre, Hervé; Granger, Bernard; Ringuenet, Damien; Tzavara, Eleni T.; Martinot, Jean‐Luc; Paillère Martinot, Marie‐Laure
Abstract : Background: Although treatment‐resistant and nontreatment‐resistant depressed patients show structural brain anomalies relative to healthy controls, the difference in regional volumetry between these two groups remains undocumented. Methods: A whole‐brain voxel‐based morphometry (VBM) analysis of regional volumes was performed in 125 participants' magnetic resonance images obtained on a 1.5 Tesla scanner; 41 had treatment‐resistant depression (TRD), 40 nontreatment‐resistant depression (non‐TRD), and 44 were healthy controls. The groups were comparable for age and gender. Bipolar/unipolar features as well as pharmacological treatment classes were taken into account as covariates. Results: TRD patients had higher gray matter (GM) volume in the left and right amygdala than non‐TRD patients. No difference was found between the TRD bipolar and the TRD unipolar patients, or between the non‐TRD bipolar and non‐TRD unipolar patients. An exploratory analysis showed that lithium‐treated patients in both groups had higher GM volume in the superior and middle frontal gyri in both hemispheres. Conclusions: Higher GM volume in amygdala detected in TRD patients might be seen in perspective with vulnerability to chronicity, revealed by medication resistance.